THE DEVELOPMENT OF THE ENGLISH LANGUAGE TEACHER’S INTERPERSONAL SKILLS IN IN-SERVICE TEACHER POFESSIONAL PROGRAM - Zuhri, Fauris; Setiawan, Slamet; Anam, Syafi'ul (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2023)
Innovative English instruction practices require knowledge and skills of teaching appropriately as an English teacher. This study aims to explain the development of English language teachers’ interpersonal skills in an in-service teacher professional program at one of the universities in Surabaya through lecturing/tutorials, seminars/workshops, and English instruction practices. Experienced English teachers need interpersonal skills to develop interactive communication with learners. Studies of interpersonal skills discussed pedagogical competence. This study focuses on interpersonal skills in pedagogical and professional competencies. However, this study focuses on developing English language teachers’ interpersonal skills in innovative English instruction development and practices in class. So, this study implements the qualitative method to find out the story of English language teachers’ interpersonal skills in innovative English instruction development and practices in class. The participants are English teachers in an in-service teacher professional program, investigated using an online observation to describe the development of English language teachers’ interpersonal skills at innovative English instruction practices. The results show that developing English language teachers’ interpersonal skills, communication, collaboration, critical thinking, and creation can increase students’ academic engagement to achieve innovative English instruction. Therefore, English teachers' capacity, capability, and innovative instructional practices can increase teachers’ knowledge, skills, and character, so they become professional English teachers. Finally, the conclusion is that developing English language teachers’ interpersonal skills can increase students’ academic engagement to achieve innovative English instruction purposes.